The Cancer Genome Anatomy Project: new resources for reading the molecular signatures of cancer - Strausberg, Robert L. (The Journal of pathology, 2001)
The Cancer Genome Anatomy Project (CGAP) has built informational, technological, and physical resources to interface genomics with basic and clinical cancer research. The CGAP web site (http://cgap.nci.nih.gov) provides informatics tools for in silico analysis of the CGAP datasets as well as information for accessing each of the CGAP resources. Published in 2001 by John Wiley & Sons, Ltd.